Higd1a facilitates exercise-mediated alleviation of fatty liver in diet-induced obese mice - Zhu, Jie-Ying; Chen, Min; Mu, Wang-Jing; Luo, Hong-Yang; Guo, Liang (Metabolism, clinical and experimental, 2022)
Nonalcoholic fatty liver disease (NAFLD) has emerged as the most common liver disease. Exercise is an effective strategy against NAFLD, but its underlying molecular mechanism is not completely understood. Higd1a, a mitochondrial inner membrane protein, was knocked down or overexpressed in mice livers by tail vein injection of adeno-associated virus (AAV) vectors. High fat diet-induced obese mice were subjected to treadmill training. Alpha mouse liver 12 (AML12) cells were used for in vitro studies. Higd1a was upregulated in mice livers after treadmill exercise training. Knockdown of Higd1a in diet-induced obese mice livers impaired exercise-mediated alleviation of hepatic steatosis, liver injury and inflammation. On the contrary, hepatic overexpression of Higd1a ameliorated fatty liver, liver injury and inflammation in synergy with exercise. Mechanistically, deficiency of Higd1a in hepatocytes promoted free fatty acids (FFAs)-induced apoptosis and oxidative stress, and elevated the cytosolic level of oxidized mitochondrial DNA (ox-mtDNA) to activate NLRP3 inflammasome and JNK signaling, leading to decreased expression of critical genes involved in fatty acid oxidation (FAO), such as Ppara, Cpt1a and Acadm. Overexpression of Higd1a in hepatocytes blunted the above effects, which ultimately increased FAO genes expression and alleviated fat accumulation in hepatocytes. These results identify a Higd1a-mediated inhibition of cytosolic ox-mtDNA/NLRP3 inflammasomes/JNK pathway that facilitates exercise-mediated alleviation of hepatosteatosis. [Display omitted] •Exercise induces the expression of Higd1a in mice livers.•Hepatic Higd1a deficiency undermines exercise-mediated alleviation of fatty liver.•Overexpression of hepatic Higd1a relieves fatty liver in synergy with exercise.•Higd1a inhibits the cytosolic ox-mtDNA/NLRP3 inflammasomes/JNK pathway.